Application of three-dimensional printing in the planning and execution of aortic aneurysm repair - Harshank Patel; Paul Choi; Jennifer C. Ku; Rosemary Vergara; Rafael Malgor; Dhiren Patel; Yong Li (Frontiers in Cardiovascular Medicine)
IntroductionThe accuracy of fenestrations in stent grafts for complex aortic aneurysms and dissections can be significantly improved using three-dimensional (3D)-printed phantoms. Standardization is enhanced by using artificial intelligence (AI) for image pre-processing before 3D printing. These methods address fallacies in centerline image analysis and manual image pre-processing. This review examines the application of 3D printing and AI in complex aortic aneurysm repair, highlighting current clinical trends.MethodsAn exhaustive literature review was performed using keywords such as “3D printing,” “Artificial intelligence,” “Thoracoabdominal aneurysm,” “Abdominal aortic aneurysm,” “Aortic arch aneurysm,” “Endovascular repair,” and “Open repair” in PubMed and Google Scholar indexes up to June 2022.ResultsThis analysis included seven studies: four focused on 3D-printed phantoms for endovascular repair of various aortic pathologies (aortic arch, thoracoabdominal aorta, juxtarenal and pararenal aorta), one on open thoracoabdominal aneurysm repair using 3D-printed models for graft construction, and two on the use of convolutional neural networks, an AI-based technology, for the pre-processing of aortic computed tomography angiography images.ConclusionThe application of 3D printing and AI-based image pre-processing in the planning of complex aortic aneurysms offers several benefits, including enhanced patient and trainee education, more accurate fenestration placement, reduced surgical time and complications, and decreased surgeon stress.